Sebaran dan Struktur Komunitas Moluska di Pantai Mertasari Kota Denpasar, Provinsi Bali - Sukawati, Ni Komang Ayu; Restu, I Wayan; Saraswati, Suprabadevi Ayumayasari (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.78-85, 2017)
The research objectives were to investigate the distribution and molluscs community structure in Mertasari beach, Denpasar-Bali. The research area was divided into 2 sites, the first site (I) has sandy substrate and second site (II) has muddy sand substrate. This research used quadrat transects systematic sampling method with 1x1 m 2 quadrat. The data of the research were analyzed used Microsoft Excel. It was conducted from January to March 2017. The research result shows that the structure of molluscs in Mertasari Beach was support by 31 species richness of 25 species from gastropods and 6 species of bivalves. The density number of the molluscs was 124.5 ind/m 2 . The diversity index of the molluscs ranged from 2.29 to 2.58 were category as moderate diversity, the evenness index ranged 0.83 to 0.87 were category as high evenness, the dominance index ranged from 0.09-0.13 were category as low. the index number indicates that the ecological condition at Mertasari beach was in good condition so it is suitable to support the molluscs community livelihood. Which was supported by water quality value of dissolved oxygen at Mertasari beach ranged from 4-6.7 mg/l, pH waters ranged from 7.39-7.74, water temperature ranged from 25.9-29 o C, water salinity ranged from 9-29 ppt. The distribution pattern of 31 species of molluscs were in groups (Id>1).